Access and management of HIV‐related diseases in resource‐constrained settings: a workshop report. (April 2016) - Dimba, EAO; Yengopal, V; Joshua, E; Thavarajah, R; Balasundaram, S
Abstract : With advancement of medical interventions, the lifespan of people living with HIV has increased globally. However, low‐ and middle‐income countries (LMICs) which bear the greatest burden of the HIV pandemic face a constant challenge in addressing the treatment needs of immune‐suppressed patients. An analysis of the current management protocols and access to medication in resource‐poor settings was conducted at this workshop, with emphasis on the situation in resource‐poor settings. The participants developed a consensus document based on the need to respond to the constantly changing HIV pandemic. Provision of oral health care must be guided by interconnecting principles based on population based strategies that address upstream determinants of health. Basic oral health coverage in developing countries can only be realized with a strong foundation at the primary health level. Early diagnosis of HIV‐related comorbidities including the adverse effects of ARVs is essential for the improvement of treatment outcomes. Standardization of oral health care delivery mechanisms will facilitate evaluation at national and regional levels. Oral health care workers have a moral obligation to participate in sustained campaigns to reduce the social stigma associated with HIV/AIDS in their work places at every stage of the referral chain. Future research also needs to realign itself towards prevention using the common risk factor approach, which has a broader impact on non‐communicable diseases, which are increasingly affecting patients with HIV/AIDS as their life expectancies increase.